Mechanical behavior of flat CFST column to steel beam joints under reversed cyclic loading. (1st November 2019) - Xu, Li; Pan, Jinlong; Cai, Jingming; Wu, Dan; Li, Yue
Highlights: A novel flat CFST column to steel beam joint is proposed. The seismic behavior of the joints is compared and discussed in various aspects. The impacts of joint type and arrangement for steel beams on the joints are studied. Abstract: Flat concrete-filled steel tubular (CFST) columns are characterized by the height-to-width ratio of the cross-section between 2 and 4. The paper investigates the reversed cyclic behavior of flat CFST column to steel beam joints, which use high-strength through-column bolts and extended end-plates for connecting the beams and columns. Four joint specimens, including two interior joints and two exterior joints, were tested under reversed cyclic loading. The position of the steel beams was considered as an experimental parameter in the test. The strength, deformation capacity, energy dissipation capacity and damage resistance capacity of the joint specimens were evaluated based on the recorded load-displacement hysteretic responses. The test results demonstrated that all joint specimens showed ductile beam hinge failure without obvious damage in the CFST columns. The ultimate inter-story drifts of the joints were 0.030–0.045, which indicated the joint specimens had sufficient deformation capacity. The joint specimens exhibited wide and stable hysteresis loops with good energy dissipation capacity. The joint specimens had a 30–40% increase in ultimate displacement and a decrease in energy dissipation as the steel beams moved from the column center to the column edge. Thus, the eccentric arrangement of steel beams contributed to the strength, deformation capacity and damage resistance capacity of the joint specimens, whereas negatively affected the energy dissipation.